Perancangan Interior Galeri Olahraga Basket di DBL Arena Surabaya - Halim, Shinta Sari (Intra, 2015)
Surabaya becomes the center of activity for its citizen, including the center of basketball which has developed since long time ago and become its local content. Most of people know about basketball without knowing its history and development. Therefore, the writer wants to design a gallery which is educative, informative, and recreational to facilitate people in giving appreciation for basketball which has been there and developed in Surabaya. The rooms are lobby, gallery area, office room, press conference room, meeting room, head chief room, collection storage, merchandise shop, cafe, kitchen, toilet, and janitor. By having this facility, the writer hopes that she can give an enjoyment for people with using attractive concept which is suitable with Surabaya peopleâs taste.